2017
DOI: 10.1108/ebr-01-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Russian railways on the Eurasian market: issue of sustainability

Abstract: Purpose This research examines factors that determine the improvement of the Russian supply chain sustainability. The strategic business model incorporates ecological, social and economic aspects. Design/methodology/approach Considering Trans-Siberian Railway as a typical case, the study selected several cases or the parts of the primary rail connection with the affiliation of important neighbouring countries. The study uses quantitative analyses of a variety of size parameters (e.g. volumes of traffic, logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Similarly, Essay III concludes that despite the complexity of the railway system in Russia, its actual carbon emissions remain close to optimal minimum, which supports the recommendation for Russian supply chains to favor the use of the railway. However, Panova et al (2017) neither discuss the economic gain of the railway company nor the fixed nature of the railway infrastructure, like we do in Essay III. Yet why?…”
Section: Theoretical Contributionmentioning
confidence: 90%
See 3 more Smart Citations
“…Similarly, Essay III concludes that despite the complexity of the railway system in Russia, its actual carbon emissions remain close to optimal minimum, which supports the recommendation for Russian supply chains to favor the use of the railway. However, Panova et al (2017) neither discuss the economic gain of the railway company nor the fixed nature of the railway infrastructure, like we do in Essay III. Yet why?…”
Section: Theoretical Contributionmentioning
confidence: 90%
“…Studying influence of internalization, along with innovativeness, risk-taking, collaboration and integration on adoption of sustainability initiatives in supply chains in Russia, Aray et al (2020) find a positive association between sustainability performance and sustainability transition being mediated by company's innovativeness and internalization. To facilitate sustainability transition of supply chains in Russia, Panova et al (2017) suggest reliance on piggyback transportation that combines both road and rail in a shipment. With a comprehensive outlook at the transport industry, including the inland waterway, maritime, air and rail in Russia, Trofimenko et al (2018) also support redistribution of both passenger and freight flows from the road and air to less energy-intensive modes, among which the rail is.…”
Section: Sustainability In Russiamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, research by Ayoub and Abdallah [28] suggested that the benefits from flexibility are reached through innovativeness and responsiveness within a supply chain. It should also be kept in mind that multimodal transport chains are imposed to transaction cost every time a transport mode is changed [23,29,30]. Technologies such as Radio Frequency Identification (RFID) [31,32] and Wireless Sensor Networks (WSN) [32] could be utilized to support supply chains involving multiple separate actors through efficient information exchange.…”
Section: Sustainable Business Models In Logisticsmentioning
confidence: 99%